Intervenções a distância para dor cervical - Fandim, Junior Vitorino (2020)
Background: Neck pain is a very common condition being the fourth in terms of years lived with disability. Remotely-delivered intervention have been growing in popularity over the past years with advances in technologies and telecommunication. Despite of the potential benefits and the increased number of trials, there is no synthesis demonstrating whether these interventions could lead to better clinical outcomes for patients with neck pain. Objectives: To evaluate the effectiveness of remotely-delivered interventions for pain and function outcomes compared to no treatment, waiting list, usual care, or any other active intervention in patients with neck pain. Search Methods: We performed databases searches on CENTRAL, MEDLINE, EMBASE, and four other databases and two trials registers up to May 2019. Selection criteria: We included randomised controlled trials that investigated the effectiveness of remotely-delivered interventions. We considered adult participants with neck pain. We included trials with remotely delivered intervention compared with no treatment, waiting list, usual care, or any other active intervention. Primary outcomes were pain intensity and physical function. Secondary outcomes were quality of life, return to work, psychological distress, painrelated psychological constructs, health service utilization and adverse events. Data collection and analysis: Two reviewers screened titles, abstracts, full text articles, extracted the data, and assessed risk of bias using The Cochrane Collaboration risk of bias assessment tool. We extracted data using a standardized form. We pooled the overall treatment using random-effect model meta-analysis. We combined results in a meta-analysis using mean difference (MD) or standardized mean difference (SMD) and 95% confidence intervals for continuous outcomes. The overall quality of evidence was assessed using the GRADE approach. We consider short, medium- and long-term follow-up. Results: We included eight randomized controlled trials (n = 867 participants). There is low quality of evidence remotely delivered intervention compared to minimal intervention was effective for improving pain in the short term (MD -21.4, 95% CI -38.2 to -4.5) and medium term (DM -12.2, 95% CI -19.6 to -4.8). And there is low quality of evidence that was effective for improving physical function in the medium term (DM -9.2, 95% CI -14.4 to -3.9). There is very low quality of evidence remotely delivered intervention compared to usual care were similar for pain improvement in the short, medium and long term and very low quality of evidence for physical function in the short, medium and long term. Also, there is very low quality of evidence remotely delivered intervention compared to similar face-to-face interventions were similar for improving pain and physical function in the short, medium and long term. No trials to date have reported adverse events or risk effects. Authors’ conclusions: Remote delivered intervention demonstrated an effect compared to minimal intervention for improving pain and physical function. However, remote delivered intervention has an effect similar to usual care in improving pain and physical function. There is still uncertainty in the evidence about the possible effectiveness of remotely-delivered interventions for people with neck pain.